Mass Production of Virus-Like Particles Using Chloroplast Genetic Engineering for Highly Immunogenic Oral Vaccine Against Fish Disease - Nakahira, Yoichi; Mizuno, Kaori; Yamashita, Hirofumi; Tsuchikura, Minami; Takeuchi, Kaoru; Shiina, Takashi; Kawakami, Hidemasa (Frontiers in Plant Science, 2021)
Nervous necrosis virus (NNV) is the causative agent of viral nervous necrosis (VNN), which is one of the most serious fish diseases leading to mass mortality in a wide range of fish species worldwide. Although a few injectable inactivated vaccines are commercially available, there is a need for more labor-saving, cost-effective, and fish-friendly immunization methods. The use of transgenic plants expressing pathogen-derived recombinant antigens as edible vaccines is an ideal way to meet these requirements. In this study, chloroplast genetic engineering was successfully utilized to overexpress the red-spotted grouper NNV capsid protein (RGNNV-CP). The RGNNV-CP accumulated at high levels in all young, mature, and old senescent leaves of transplastomic tobacco plants (averaging approximately 3 mg/g leaf fresh weight). The RGNNV-CP efficiently self-assembled into virus-like particles (RGNNV-VLPs) in the chloroplast stroma of the transgenic lines, which could be readily observed by in situ transmission electron microscopy. Furthermore, intraperitoneal injection and oral administration of the crudely purified protein extract containing chloroplast-derived RGNNV-VLPs provided the sevenband grouper fish with sufficient protection against RGNNV challenge, and its immunogenicity was comparable to that of a commercial injectable vaccine. These findings indicate that chloroplast-derived VLP vaccines may play a promising role in the prevention of various diseases, not only in fish but also in other animals, including humans.